TINJAUAN FIQIH MAWARIS TERHADAP PEMBAGIAN WARIS SAUDARA LAKI-LAKI SEKANDUNG DI DESA PENGARAYAN KECAMATAN TANJUNG LUBUK KABUPATEN OGAN KOMERING ILIR OKI - Lulu Allyatu Al Aulia; M Zuhdi Imron; Yusida Fitriyanti (Program Studi Al-Ahwal Al-Syakhshiyyah, 2021)
Inheritance in Islam has a very clear source of law in the Al-Quran and Hadith, but there are still many Muslim communities who carry out inheritance practices not based on Islamic inheritance law but make custom as the law that applies to the local community. This also happens to the people of Pengarayan Village, Ogan Komring Ilir where according to tradition only the descendants of the eldest son can control the inheritance from the heir if when the heir dies and there is no male heir, then the heirs of the simayit inherit the property. passed to the eldest simayit simayit even though he was still another heir. This research method uses field research methods, the source of the data used is the primary data source obtained from interviews with respondents in the field, then secondary data is obtained from books and scientific works. Data collection techniques are direct interviews, field surveys and documentation. The data analysis used is inductive qualitative, namely drawing conclusions from general statements drawn from specific statements. Then the results of the study were obtained, namely: the implementation of the distribution of the inheritance of the Pengarayan Village community based on the tradition of the distribution being carried out by family deliberation, where only male descendants distribute and control the inheritance. If there is no son, he will support a simayit simayit who will control all the inheritance, for female heirs such as mother, wife and daughters, they do not get the inheritance. Keywords :Tradition, Siblings, Islamic Inheritance Law